Kidney function profile before, during, and after Ramadan fasting in healthy elderly: a prospective cohort study (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND Kidney function profile is one of the important parameters in determining the health of the elderly. In Indonesia, no study has been conducted on kidney function profile during Ramadan fasting to determine the safety of Ramadan fasting in the elderly. This study aimed to determine the kidney function profile in the elderly who fasted during Ramadan. METHODS This study used a prospective cohort design. The inclusion criteria were elderly aged >60 years undergoing Ramadan fasting in Jatinegara, Jakarta from April to July 2019. Patients with end-stage renal failure who had an acute infection, hypertension crisis, or refused to participate in the study were excluded. Patients who did not fast for 3 consecutive days were dropped out. The kidney function profile was calculated by the estimated glomerular filtration rate (eGFR) using the CKD-EPI formula 1 week before the first day of Ramadan, 3 weeks after the first day of fasting, and 2 weeks after the last day of fasting. Decreased eGFR was defined as having a minimum of 20% eGFR decline during or after the fasting period. Bivariate analysis was performed using McNemar or Cochran tests. RESULTS 2 patients had eGFR decline during fasting, and 7 patients had eGFR decline after fasting. The median eGFR before, during, and after fasting were 81.5, 88.7, and 76.8 ml/min/1.73 m², respectively. A total of 1.4% of subjects had decreased eGFR during Ramadan, while 9.1% had decreased eGFR after Ramadan. However, the changes were not statistically significant. CONCLUSIONS Although most elderly had lower eGFR following Ramadan fasting compared to before and during Ramadan, only individuals with several comorbidities had significant changes of kidney function.